BET306 – Ekologi Serangga (Insect Ecology) July/August 2023 - Pusat Pengajian Sains Kajihayat, PPSK (Universiti Sains Malaysia, 2023)
Second Semester Examination 2022/2023 Academic Session July/August 2023 BET306 – Ekologi Serangga (Insect Ecology) Duration: 2 hours (Masa : 2 jam)